Dissolution of cotton cellulose in 1:1 mixtures of 1-butyl-3-methylimidazolium methylphosphonate and 1-alkylimidazole co-solvents. (1st October 2019) - Dissanayake, Niwanthi; Thalangamaarachchige, Vidura D.; Thakurathi, Mahesh; Knight, Matthew; Quitevis, Edward L.; Abidi, Noureddine
Highlights: Dissolution of cotton cellulose in ionic liquids is enhanced by using co-solvent. Co-solvent affects basicity, conductivity, and viscosity of ionic liquid/co-solvent. The addition of 1-alkylimidazole increases mass transport and reduces viscosity. Abstract: During the past decade, ionic liquids (ILs) have attracted increasing attention as efficient, novel solvents for dissolving cellulose. In this study, 1-butyl-3-methylimdazolium methylphosphonate ([C4 C1 im][(OMe)(H)PO2 ]) was used in the dissolution of cotton cellulose and the role of 1-methylimidazole, 1-ethylimidazole, 1-propylimidazole, and 1-butylimidazole as co-solvents was investigated. The progress of the dissolution was monitored using polarized light microscopy (PLM) and the regenerated cellulose was characterized using scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. The effect of 1-alkylimidazoles as co-solvents in cellulose dissolution was examined in terms of the basicity (hydrogen-bond acceptor capability), conductivity, viscosity, and ionicity of the IL and IL/co-solvent mixtures. These studies showed that the addition of 1-alkylimidazole co-solvents enhances cellulose dissolution by the IL and that the role of these co-solvents is mainly to increase mass transport by reducing the viscosity of the mixtures.